The influence of environmental thermal radiation on the results of thermographic investigation of buildings - Nowak, Henryk (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Thermal diagnostics of building objects, mainly of residential buildings is currently realized with the standard method of thermographic examinations which enables the search the state of the thermal insulation of building envelope, the location of thermal bridges, defects in installations of different types, places of the moisture of barriers and the excessive infiltration of air. However, the operator of the IR-camera must have the solid knowledge in the range of thermograms interpretation. Thermal radiation of the outside environment is one of many factors affecting the results of thermal imaging measurements. The article presents a general description of the thermal radiation influence of the outside environment on buildings, the importance of radiative cooling of building envelope and the influence of this radiation on thermal imaging inspections of buildings and on interpretation of thermograms.